The Empirical Investigation Between Ethical Leadership and Knowledge-Hiding Behavior in Financial Service Sector: A Moderated-Mediated Model - Mohsin, Muhammad; Zhu, Qiang; Wang, Xiaojun; Naseem, Sobia; Nazam, Muhammad (Frontiers in Psychology, 2021)
This study aims to investigate the impact of ethical leadership on knowledge hiding behavior of the employees working in the financial services sector under the mediating role of meaningful at work and moderating role of ethical climate. For this purpose, data were collected from two hundred and fifteen employees of financial services providing organizations. Already established scales were followed to develop an instrument that was used to obtain responses from the respondents. Collected data were analyzed by applying the structural equation modeling through Smart PLS and Process Macro. Results indicate that ethical leadership and meaningful work reduce knowledge hiding behavior of employees at work while ethical leadership positively impacts the influential work of employees at the workplace. Further, the relationship between ethical leadership and knowledge hiding behavior is partially mediated by meaningful work. Similarly, ethical climate moderated the relationship between ethical leadership knowledge hiding. This research makes valuable contributions to the existing literature on leadership and knowledge management. From a practical point of view, this study stresses that managers at work should promote ethical leadership styles to promote meaningful work, which will reduce knowledge hiding. Thus, in this way, it will enhance the innovation and creativity within organizational circuits. Limitations and future directions of the study are also listed.